Multimodal Ultrasound Imaging in the Diagnosis of Primary Giant Cell Tumor of the Breast: A Case Report and Literature Review - Chen, Fei; Chen, Yu‐Jia; Hu, Yan‐Ze (Journal of clinical ultrasound, 2025)
ABSTRACT Giant cell tumor of soft tissue (GCT‐ST) is an extremely rare phenomenon in the breast. Herein, a case involving a 75‐year‐old female with a painless lump and bloody discharge from the nipple of her left breast is reported. A diagnosis of malignant tumor was arrived at by observing the location of the tumor, interior echo, margins, vascular distribution, hardness, and microvascular density on preoperative multimodal ultrasonography. However, no evidence of malignancy was found on ultrasonography‐guided nuclear needle biopsy or rapid intraoperative pathological examination. Subsequently, an excisional biopsy was performed, and GCT‐ST coincident with high‐grade ductal carcinoma in situ were confirmed using histopathology and immunohistochemistry. Accordingly, the patient underwent left‐sided mastectomy and sentinel lymph node biopsy. This case emphasizes the complexity of the clinical and pathological diagnosis of GCT‐ST in the breast and may raise the awareness of clinicians and sonographers to the advantages of multimodal ultrasound imaging in the diagnosis of GCT‐ST in the breast. Pathologists should consider the possibility of GCT‐ST when encountering a giant cell‐rich mass in the breast.